2021
DOI: 10.14814/phy2.15009
|View full text |Cite
|
Sign up to set email alerts
|

Mini‐review: Glucagon responses in type 1 diabetes – a matter of complexity

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
(88 reference statements)
1
19
1
Order By: Relevance
“…Previous studies have reported that patients with T1DM excessively secrete glucagon after a mixed-meal stimulation as opposed to individuals without diabetes [13]. In healthy individuals, blood glucagon levels reach a peak 30 -60 min after consuming a mixed-meal (700 kcal; 100 g of carbohydrate, 26 g of protein, and 22 g of fat), return to near baseline after 120 min, then increase again; however, the range of fluctuation is small compared to patients with diabetes [14].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported that patients with T1DM excessively secrete glucagon after a mixed-meal stimulation as opposed to individuals without diabetes [13]. In healthy individuals, blood glucagon levels reach a peak 30 -60 min after consuming a mixed-meal (700 kcal; 100 g of carbohydrate, 26 g of protein, and 22 g of fat), return to near baseline after 120 min, then increase again; however, the range of fluctuation is small compared to patients with diabetes [14].…”
Section: Discussionmentioning
confidence: 97%
“…In healthy individuals, blood glucagon levels reach a peak 30 -60 min after consuming a mixed-meal (700 kcal; 100 g of carbohydrate, 26 g of protein, and 22 g of fat), return to near baseline after 120 min, then increase again; however, the range of fluctuation is small compared to patients with diabetes [14]. The excessive secretion of glucagon after a mixed-meal stimulation in pa-tients with T1DM relates to low paracrine insulin secretion, which could cause postprandial hyperglycemia due to hyperglucagonemia in patients with T1DM [13].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, type 1 diabetes increases the risk of associated autoimmune disease, including adrenocortical failure, and people with concomitant Addison disease and type 1 diabetes have increased risk both of hypoglycemia and adrenal crisis [ 64 , 65 ]. It would appear advisable to incorporate the existence of additional organ dysfunction including HAAF in the setting of therapeutic targets, perhaps aiming at less-strict glycemic windows in closed-loop systems likely to dominate the future; adding adjustable glucagon infusion to such systems could be considered in selected patients with defective counterregulation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…110,111 Individuals with T2DM, as opposed to nondiabetic subjects, display glucagon hypersecretion after meals, thereby potentially contributing to insulin resistance. 112 Thus, patients with diabetes have lost the first two lines of defense and are particularly vulnerable to changes in epinephrine release, [113][114][115] which further increases the risk of recurrent and severe hypoglycemia. 116 In addition to these well-described counter-regulatory hormonal responses, the central nervous system (CNS) also plays a critical role in the response to hypoglycemia (Figure 1).…”
Section: Physiologic Defenses Against Hypoglycemiamentioning
confidence: 99%
“…Furthermore, β‐cell destruction is also linked to the loss of α‐cell glucagon secretory response to hypoglycemia which prevents hypoglycemia‐triggered increases in glucagon levels 110,111 . Individuals with T2DM, as opposed to nondiabetic subjects, display glucagon hypersecretion after meals, thereby potentially contributing to insulin resistance 112 . Thus, patients with diabetes have lost the first two lines of defense and are particularly vulnerable to changes in epinephrine release, 113–115 which further increases the risk of recurrent and severe hypoglycemia 116 …”
Section: Introductionmentioning
confidence: 99%